(untitled) (IUS LAW Journal, 2025)
The right to early repayment or repayment of the loan has a significant protective role for the consumer, who, especially in circumstances of lending need and under the pressure of a difficult economic situation, may find himself "trapped" in multi-year loan arrangements from which it is not easy for him to escape. In addition to an important protective role, the right to early loan repayment is also an instrument for stimulating market competition by enabling greater mobility of clients of loan institutions, i.e. consumers themselves. This right enables the consumer, especially when he has the means to settle existing obligations or has the opportunity to borrow from another loan provider under more favorable conditions, fulfill his contractual obligation towards the loan provider earlier, and thus save part of the interest amount. If there were no mentioned or similar mechanisms, the loan consumer would be "hostage" of the loan and the costs it carries, regardless of the possible possibilities to repay the loan debt earlier and thus free from unnecessary interest costs for the remaining repayment period.